2007
DOI: 10.1055/s-2007-965614
|View full text |Cite
|
Sign up to set email alerts
|

Floral Scent in Food‐Deceptive Orchids: Species Specificity and Sources of Variability

Abstract: One third of all orchid species are deceptive and do not reward their pollinators. Such deceptive orchids are often characterised by unusually high variation in floral signals such as colour and scent. In this study, we investigated the scent composition of two Mediterranean food-deceptive orchids Orchis mascula, Orchis pauciflora, and their hybrid, O. x colemanii. Scent was collected IN SITU by headspace sorption and was subsequently analysed with gas chromatography and gas chromatography-mass spectrometry. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 58 publications
1
51
2
3
Order By: Relevance
“…Empirical studies have shown that phenotypic and genetic variation in nectar traits can have signiÞcant direct and indirect impacts on pollination success (Galen and Newport 1988, Mitchell 2004, Salzmann et al 2007, Majetic et al 2009). In our study, pistillate ßowers produced signiÞcantly more nectar than staminate ßowers.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies have shown that phenotypic and genetic variation in nectar traits can have signiÞcant direct and indirect impacts on pollination success (Galen and Newport 1988, Mitchell 2004, Salzmann et al 2007, Majetic et al 2009). In our study, pistillate ßowers produced signiÞcantly more nectar than staminate ßowers.…”
Section: Discussionmentioning
confidence: 99%
“…Floral scents usually advertise a food source provided by the flowers. In deceptive plants, however, flower scents are a false promise of a reward, such as food, a mating partner or an oviposition site (Salzmann et al, 2007;Jürgens et al, 2013;Bohmann et al, 2014) that these plants do not actually offer. Among these cheaters are plants of the genus Ceropegia L. (Apocynaceae, Asclepiadoideae) with more than 200 described species, characterized by sophisticated pitfall flowers (Vogel, 1961;Masinde, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Only as a rare exception, flowers emit single compounds Wiemer et al 2009), but usually fragrance consists of complex blends of VOCs originating from different biosynthetic pathways (Raguso 2008). Such bouquets are often taxon-or population specific, by means of different qualitative composition, or just different proportions of the same compounds (Chess et al 2008;Huber et al 2005;Mant et al 2005;Salzmann et al 2007a). Different compounds in a bouquet can have different functions, thus the production of a range of different compounds can help the plant to fulfill different tasks in its interaction with other organisms.…”
Section: Introductionmentioning
confidence: 99%